Processing perspectives on task performance - Skehan, Peter (Task-based language teaching ;, 2014)
This chapter reports on a study of video-based narrative retellings, in which the major variables are degree of structure and the nature of the processing conditions under which the retellings were done. The two variables were manipulated in a 4 × 4 design. Four Mr. Bean video clips were used, with different levels of structure, ranging from no structure to a clear, well organised problem-solution structure. In addition to a control group, there were two online processing conditions (opportunity to pause, and provision of a summary before the task), and one offline Watch-then-Tell condition. T.